Sun Pharmaceutical Industries Limited : a star player for portfolio managers? - Mohapatra, Amrit; Gupta, Gaurav K.; Chaurasia, Ashish (London : SAGE Publications: SAGE Business Cases Originals, 2022)
Sun Pharmaceutical Industries Limited (SPIL) is India's largest pharmaceutical company in terms of market share and is an industry driver for the pharma sector. Starting in 2015, the company's growth prospects had been on decline, and this trend continued until the pre-COVID outbreak period. However, the pandemic offered the opportunity for the recovery and growth of the company. This case allows students to assess the company by employing the economy, industry, and company (EIC) framework. This method is a top-down approach that aims to understand whether the firm's stocks are safe to invest in based on intrinsic valuation using the discounted cash flow to the firm and dividend discounting model concept.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Investments -- India -- Case studies; Cash flow -- Case studies